Random Forest population modelling of striped and common-bottlenose dolphins in the Gulf of Taranto (Northern Ionian Sea, Central-eastern Mediterranean Sea). (1st May 2018) - Carlucci, Roberto; Cipriano, Giulia; Paoli, Chiara; Ricci, Pasquale; Fanizza, Carmelo; Capezzuto, Francesca; Vassallo, Paolo
Abstract: This study provides the first estimates of density and abundance of the striped dolphin Stenella coeruleoalba and common bottlenose dolphin Tursiops truncatus in the Gulf of Taranto (Northern Ionian Sea, Central Mediterranean Sea) and identifies the predictive variables mainly influencing their occurrence and concentration in the study area. Conventional Distance Sampling (CDS) and the Delta approach on Random Forest (DaRF) methods have been applied to sightings data collected between 2009 and 2016 during standardized vessel-based surveys, providing similar outcomes. The mean value of density over the entire study area was 0.72 ± 0.26 specimens/km 2 for the striped dolphin and 0.47 ± 0.09 specimens/km 2 for the common bottlenose dolphin. The abundance estimated by DaRF in the Gulf of Taranto was 10080 ± 3584 specimens of S. coeruleoalba and 6580 ± 1270 specimens of T. truncatus, respectively. Eight predictive variables were selected, considering both the local physiographic features and human activities existing in the investigated area. The explanatory variables depth, distance from the coast, distance from industrial areas and distance from areas exploited by fishery seem to play a key role in influencing the spatial distribution of both species, whereas the geomorphological variables proved to be the most significant factors shaping the concentration of both dolphins. The establishment of a Specially Protected Area of Mediterranean Importance (SPAMI) according the SPA/BD Protocol in the Gulf of Taranto is indicated as an effective management tool for the conservation of both dolphin populations in the Central-eastern Mediterranean Sea. Highlights: Density and abundance estimates for S. coeruleoalba and T. truncatus were provided. Conventional Distance Sampling and Delta approach on Random Forest regression methods were applied. Main variables affecting the occurrence and concentration of both species were identified.